Kesehatan Mental Remaja: Tinjauan Psikososial dan Lingkungan - Pratama, Farel; Pratiwi, Dessy (Lembaga Publikasi Ilmiah Nusantara, 2025)
Adolescence is a transitional period filled with developmental challenges, both biologically, psychologically, and socially. Adolescent mental health is influenced by various interrelated factors, including psychosocial and environmental aspects. This study aims to comprehensively review the influence of psychosocial aspects, such as family support, peer interactions, and academic pressure, as well as environmental factors, including school conditions, digital environments, and community settings, on adolescent mental health. The research method used is a literature review by analyzing relevant articles and journals from the past ten years. The findings indicate that psychosocial factors play a dominant role in determining adolescent mental health. Adolescents who receive emotional support from family and peers tend to have lower stress levels and better mental well-being. Conversely, low social support, bullying, and excessive academic demands contribute to increased risks of depression, anxiety, and deviant behaviors. Environmental factors, particularly exposure to social media and school conditions, are also shown to have a significant impact. A healthy, safe, and inclusive environment can serve as a protective factor for adolescent mental health. The conclusion of this review is that adolescent mental health is not only influenced by internal factors but is also strongly shaped by the social and environmental contexts in which they grow and develop. Therefore, promotive and preventive efforts for adolescent mental health must involve families, schools, and communities collaboratively to create an ecosystem that supports healthy psychological development.